2020
DOI: 10.3389/fonc.2020.00998
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Induced lncRNA-NEAT1 Sustains the Growth of Hepatocellular Carcinoma via Regulation of miR-199a-3p/UCK2

Abstract: The long noncoding RNA (lncRNA) nuclear paraspeckle assembly transcript 1 (NEAT1) has emerged as a novel player in hepatocellular carcinoma (HCC). Hypoxia is a common characteristic of the microenvironment of HCC. This study aimed to investigate whether lncRNA-NEAT1 is induced by hypoxia in HCC, and the mechanism that underlies LncRNA-NEAT1 function. Methods: The expression changes of lncRNA-NEAT1 in HCC cell lines under hypoxic conditions were examined by quantitative reverse transcription-polymerase chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…In the process of melanoma cancer, an aberrant activation of the Wnt/β-catenin signaling pathway can be found (25,26). Nevertheless, UCK2 has an uncertain relationship with the Wnt/β-catenin pathway in melanoma.…”
Section: T H E P Y R I M I D I N E R I B O N U C L E O T I D E K I N a S E U C K 2 Can Catalyze Phosphorylation Of Uridine-to-uridine Monmentioning
confidence: 99%
“…In the process of melanoma cancer, an aberrant activation of the Wnt/β-catenin signaling pathway can be found (25,26). Nevertheless, UCK2 has an uncertain relationship with the Wnt/β-catenin pathway in melanoma.…”
Section: T H E P Y R I M I D I N E R I B O N U C L E O T I D E K I N a S E U C K 2 Can Catalyze Phosphorylation Of Uridine-to-uridine Monmentioning
confidence: 99%
“…Specifically, activation of LncRNA-NEAT1 (another architectural component of nuclear paraspeckles) in response to hypoxia has been reported [27]. In vitro studies have demonstrated that HIF1α regulates LncRNA-NEAT1 transcription, maintaining cancer cell growth and inhibiting their apoptosis and cell cycle arrest [28]. The potential contribution of hypoxia to PSPC1 expression could be relevant in tumor cells, given that hypoxia is a common characteristic of the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, miRNAs in different tumors may have different functions. In hypoxia-induced HCC, miR-199a-3p [30], miR-512-3p [31], miR-3677-3p [32], and miR-140 [33] have been found to be aberrantly expressed. Although miR-3156-5p's expression and role in HCC have not been investigated, it is highly expressed in breast cancer tissues [11] and colorectal cancer tissues [34] and is associated with malignant tumor development.…”
Section: Discussionmentioning
confidence: 99%